All Balls and Glitter : My Life - Horwood, Craig Revel and Maloney, Alison (London Michael O'Mara, 2008)
As the most outspoken judge on Strictly Come Dancing, Craig Revel Horwood is no stranger to controversy and is notorious for his cutting put-downs and often brutal honesty. This autobiography tells his life story, beginning with his childhood in Australia, and spills the secrets of his celebrity encounters.
Include Color Illustration and Index
Keywords: Horwood, Craig Revel -- Television personalities -- Australia